Rancangan Sistem Informasi Kegiatan Masjid Berbasis Web (Studi Kasus: Masjid Suciati Saliman) - Maulia Atikah Azmi; Aridhanyati Arifin S.T., M.Cs (AUTOMATA, 2020)
Suciati Saliman Mosque is one of the Great Mosque that has many worshipers. Suciati Saliman Mosque is located in Gito Gati Street, Grojogan, Pandowoharjp, Sleman. The number of activities that held at the Suciati Saliman Mosque whose publications are still limited, makes it difficult for many people to get information. Suciati Saliman Mosque also does not have a system or media to share that can be easily accessed by everyone. For this reason, it is need to design a web-based information system about all the activities that can be accessed anywhere and anytime by everyone, The stages of this research include data collection by interviewing, analyzing data, then designing use case diagrams, activity diagrams, databases, and prototype.